Evaluation of some intestinal cytokines genes expression and serum innate immune parameters in common carp (Cyprinus carpio) fed dietary loquat (Eriobotrya japonica) leaf extract - Seyed Hossein Hoseinifar (2018)
© 2017 John Wiley & Sons Ltd The aim of this study was to illustrate the effects of dietary loquat leaf extract (LLE) on the expression of some intestinal cytokines as well as serum innate immune parameters in common carp (Cyprinus carpio) fingerlings. The fish were fed with experimental diets supplemented with 0 (control), 0.25% (0.25LLE), 0.5% (0.5LLE) and 1% (1LLE) LLE over a 7-week period. At the end of the trial, the serum lysozyme (Lys) activity, ACH50, total Ig as well as the expression of IL1B, IL8, TNF-alpha, LYZ and TGF-β in intestine were evaluated. The results showed that administration of 0.5% or 1% LLE significantly increased serum total Ig. However, in case of serum Lys activity significant elevation was observed just in fish fed 0.5% LLE. Also, supplementation of diet with LLE significantly increased ACH50 compared to the control group, regardless of inclusion levels. Gene expression studies re vealed upregulation of TNF-alpha, IL1B, IL8 and LYZ in intestine of fish fed LLE. However, the effects varied dependent on LLE levels and the tested immune related gene. Also, in case of TGF-β significant downregulation was observed just in 1% LLE treatment. In conclusion, dietary LLE supplementation significantly upregulated immune related genes in intestine and improves innate immune responses. Altogether, LLE can be recommended as fish immunostimulant in early stage of carp culture.